Arti Seorang Pendidik Untuk “Kids Zaman Now” - Umi Musya'adah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
Educate your children, becuse they will live in different periode than yours” (Umar bin Khattab). This short message is remindable and meant that science is dinamic. Todays, the educator is more than only parent in the home or teacher in the class, because his prime duty is to guide and lead the children to the maturity. The latest children that involved by social networking in social media known in Indonesia as “kids zaman now” (kids of the periode) they are described as the generation reach maturity faster than before and susceptible to take anything without limitation whether in norm value or religion value. Because of that, the bigest challenge of parents and teachers is how to educate the children based on their period. However, educating and leading the children is a duty and respponsibility of family, school, society, and whether state. Once again, this is a big challenge of the educators in Indonesia, moreover, the children are the most valuable asset of the nation. All bad posibilities will be happened when the children of the state and nation involved by unvaluable things can bring degradation even damage.